Diseño de un producto editorial ilustrado para la puesta en valor de una comunidad en la provicncia de Cotopaxi. - Cócheres Sandoval, José Eduardo (2018)
The research was realized to combat the central problem which is: the few printed editorial products about the visual transmission regarding the cultural and patrimonial value of the Quilotoa community, also the issue of the scarce of existing visual resources from the crafts’ processes and workflows of the sector; since it was not evident in the surroundings any editorial product to report their work. For this purpose, the current situation of the community and the local development of the town, especially in the artisanal sector, was investigated and diagnosed. For this, data collection techniques were used, such as: observation, interview and survey. A bibliographic research with experimental design was carried out through a synthetic analysis to determine theoretical concepts that facilitate the support of the research, these theories range from editorial design, to graphic elements for the construction of the project. As methodology of the project, was used a design methodology of Guillermo González Ruiz, which allowed to capture graphic information such as: photographs of the sector, illustrations that are based on the Semi-Naif trend where colors and illustration stand out, techniques and Handicraft production processes such as: masks carved in wood, paintings made in sheepskin and fabrics. This methodology was carried out through stages that start in the ideas and sketches until the construction of the product facilitating each editorial process. Contributions from the research mainly benefited the 350 craftsmen partners of the community. The magazine called "Maki Rurana", which contains tourist references, experiences, process of creation of handicrafts and undertakings of the sector, becoming a communicational platform showing the intangible heritage of the community. Obtaining as results a functional and communicational aesthetic editorial product.